MUCOADHESIVE BUCCAL DRUG DELIVERY SYSTEM: REVIEW ARTICLE - Sonawane, Monali; Shinkar, Dattatrey; ., Ravindrasaudagar (International Journal of Current Pharmaceutical Research, 2017)
The advantage of buccal drug delivery system over the conventional and systemic formulation majority. It helps enhance the bioavailability through bypassing the first-pass metabolism effect. The mucosal surface better absorption and prolong resident time. Bioadhesion can be defined as the phenomenon of interfacial molecular attractive force in midst of the surface of the biological substrate and the natural or synthetic polymers, which allows the polymers to adher to the biological surface for an extended period of time. Among the various transmucosal sites available, mucosa of the buccal cavity was found to be the most convenient and easily approachable site for the delivery of the therapeutic agent for both local and systemic delivery. This review also covers available marketed product as buccal drug delivery system and future aspects of buccal drug delivery system.